A Study of Tracker Software-assisted Spring Coupled Pendulum Oscillation - Aprilia, Ananda; Dwandaru, Wipsar Sunu Brams (Universitas Ahmad Dahlan, 2023)
Oscillatory motions are an essential part of our physical world. These motions need to be studied and learned by students. However, complicated oscillatory motions, e.g.: spring coupled pendulum, are rarely taught to students because their analytical solutions (if they exist) are complicated Here, we use the Tracker software to bridge between the actual coupled pendulum oscillation and its analytical solution. This study aimed to determine the period and frequency of Tracker software-assisted spring coupled pendulum oscillations. The displacement of the pendulum is divided into in-phase and out-of-phase motions. Data collection was carried out by recording the oscillatory motions up to 10 oscillations. The data were obtained from the pendulum position with respect to time. The data analysis techniques in this study used two methods, namely: i) Tracker software and ii) analytical calculations. The results showed that the period and frequency obtained via the Tracker software were in accordance with the analytical calculations. The periods of the in-phase motion and analytical calculation were 1.42 s and 1.54 s, respectively. The periods of the out-of-phase motions and analytical calculation were 0.7 s and 0.55 s, respectively. The frequencies of the in-phase motion and analytical calculation were 0.70 Hz and 0.65 Hz, respectively. The frequencies of the out-of-phase motions and analytical calculation were 1.50 Hz and 1.83 Hz, respectively. The uncertainty values of the results were 7% to 22%. Hence, the spring coupled pendulum oscillations became tractable and can be compared to the analytical solution.